Lexical Availability Among Young Palenquero Creole Speakers: A Sociolinguistic Analysis - Valdez Jiménez, Wendy; Díaz Pérez, Mirian; Pulgarín Rivera, Juan Diego; De La Rosa Yacomelo, Johan (Íkala, Revista de Lenguaje y Cultura, 2025)
This article explores lexical availability in Palenquero Creole among bilingual students enrolled in 5th and 11th school grades at the Benkos Biohó Peasant Ethnic Educational Institution in the village of San Basilio de Palenque (Colombia). This study was conducted against the backdrop of a language revitalization process. To measure lexical availability sociocultural surveys, a bilingualism test, and a lexical availability test based on 17 thematic fields of interest were applied using a sociolinguistic and quantitative approach. Findings suggest that the family domain manifests greater lexical availability and cohesion, whereas technical domains exhibit lower frequency and diversity, reflecting the effects of diglossia and the influence of Spanish. Although no gender-based differences were found, statistically significant differences by grade level were observed, suggesting that schooling is an indirect indicator of competence in Palenquero Creole. This study contributes to filling a gap in research on lexical availability in Creole languages, as most previous studies have focused on monolingual or bilingual communities rather than in minoritized languages undergoing revitalization. These findings provide empirical evidence for understanding bilingualism and revitalization processes, and offer recommendations to strengthen the teaching and use of the language.